Photographs from another place deciphering a forgotten photographic archive - its characters, artefacts, stories & geography - Szirtes, George 1948-; Govier, David (Dewi Lewis Publishing, 2019)
In 2014 Alan J. Ward purchased a collection of 'quarter plate' glass negatives on a whim, from an Ebay seller in Brighton, that had no provenance. There are about 230 in total, dating from 1914 through to the 50s. Through a few clues offered up in the images and the original boxes they came in, he pieced together the beginnings of a substantial lost family history, that seemed strangely to parallel his own. Through a forensic research process and an almost voyeuristic obsession with this collection, new photographic work evolved in response to the locations, subjects and objects in the images. Intrigued by the odd, and easily overlooked elements and repeating motifs of the collection, Ward explores the forgotten, lost, ordinary, and extraordinary distant voices and still lives of the archive. The book includes a companion text by author George Szirtes, 'Gearing: a coincidence', and an interview between Alan Ward and archivist David Govier 'Unlocking the boxes' which explores the role of research in contemporary artistic practice
Wendebuch
Keywords: Gearing, Simeon J.; Ward, Alan J.; Gearing, Sydney J.; Geschichte 2014-2019; Geschichte 1914-1960; Schwarzweißfotografie; Fotografische Platte; Fotografie; Rezeption; Fotoarchiv; Photography / England / Liverpool / History / 20th century; Portrait photography / England / Liverpool / History / 20th century; Gearing family; Liverpool (England) / Genealogy; Liverpool (England) / Social life and customs / 20th century / Pictorial works; Liverpool (England) / History / 20th century / Pictorial works; Manners and customs; Photography; Portrait photography; England / Liverpool; 1900-1999; Genealogy; History; Pictorial works; Bildband